Development of E-LKPD Creative Product Business Analysis Entrepreneurship-Based to Form Independence Character Vocational Students - Dian Krisnawati; Hariyani, Sri; Tatik Retno Murniasih (Universitas Ma'arif Lampung, 2024)
A number of questionnaires with 3 options (work, entrepreneurship, and continuing to a higher school level) were given to students of SMK NU Sunan Ampel Poncokusumo Malang. The findings showed that most students chose work and entrepreneurship compared to continuing to a higher school level. Therefore, students need to be equipped with insight into business analysis, so that students are able to manage their business properly. The purpose of this study was to develop an Electronic Learner Worksheet (E-LKPD) of entrepreneurship-based creative product business analysis to form the character of student independence that meets the validity requirements. ADDIE development model was used in this research, namely: analyzing the achievement of core competencies and basic competencies of SMK (Vocational High School), learning resources used, ongoing learning situations, and the level of understanding of Vocational students of business analysis material; designing E-LKPD business analysis and research instruments in the form of material validation sheets and E-LKPD media validation sheets; and analyzing validity data using validation sheets. The results showed the material validity test to assess competence in E-LKPD was 81.25% and the media validity test was 93.75%. The business analysis material fulfills relevant aspects for learner independence and presents information that can measure the level of understanding of students.